Elementary Molecular Mechanisms of the Spontaneous Point Mutations in DNA: A Novel Quantum-Chemical Insight into the Classical Understanding - Brovarets‘, Ol'ha O.; Kolomiets‘, Iryna M.; Hovorun, Dmytro M. (IntechOpen, 2012)
None